The International Bean Rust Nursery format - Schwartz, Howard F. (1980)
A description is given of the format of the International Bean Rust Nursery (IBRN) established during a 1974 workshop of research workers from various countries. The objectives of the IBRN are to (a) identify cv. and breeding lines resistant to a wide spectrum of the pathogenic potential inherent to Uromyces phaseoli; (b) determine the stability of different types of plant resistance by time and location; (c) detect new and more virulent rust race complexes before they, or bean cv. susceptible to them, become widely disseminated; and (d) obtain information on race patterns present in bean growing regions. The IBRN entries are evaluated for their resistance 20-40 and 40-60 days after germination. (CIAT)